1983
DOI: 10.1177/089686088300300212
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Studies of Erythropoiesis during Continuous Ambulatory Peritoneal Dialysis

Abstract: In order to understand the effect of CAPD on the anemia of chronic renal failure, we studied the behaviour of some hematological parameters and of the colony-formation capacity of bone marrow cells in in vitro cultures in patients undergoing this therapy. Our studies showed a rise in hematocrit, hemoglobin and reticulocyte values, which showed a significant correlation with a recovery of the erythroid cell proliferative activity. Since serum erythropoietin levels do not change, the improvement of bone-marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In addition, we have seen an increase in RBC mass and a decrease in plasma volume (12,24). This may be explained by the more efficient removal of middle-molecular-weight molecules with CAPD (13,22,24,25), which may act as inhibitors of erythropoiesis (16). Adding sera from uremic nondialyzed patients leads to inhibition of formation of CFU-E and erythroid burst-forming units (26).…”
Section: Differences Between Peritoneal Dialysis and Hemodialysis Thamentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, we have seen an increase in RBC mass and a decrease in plasma volume (12,24). This may be explained by the more efficient removal of middle-molecular-weight molecules with CAPD (13,22,24,25), which may act as inhibitors of erythropoiesis (16). Adding sera from uremic nondialyzed patients leads to inhibition of formation of CFU-E and erythroid burst-forming units (26).…”
Section: Differences Between Peritoneal Dialysis and Hemodialysis Thamentioning
confidence: 88%
“…Due to the recovery of proliferative activity of the erythroid cells, serum ferritin and iron levels will fall. Therefore, the early use of oral iron supplementation is warranted (16).…”
Section: Oral Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] A lower degree of anaemia in CAPD patients than in HD patients has been documented in numerous studies. [6][7][8][9][10] It has been suggested that CAPD facilitates increased erythropoietin production compared to haemodialysis, as well as a better depuration of toxic metabolites inhibiting erythropoiesis. [6][7][8][9][10][11][12] However, information regarding the influence of iron metabolism on differences in the severity of anaemia between CAPD and HD patients is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] It has been suggested that CAPD facilitates increased erythropoietin production compared to haemodialysis, as well as a better depuration of toxic metabolites inhibiting erythropoiesis. [6][7][8][9][10][11][12] However, information regarding the influence of iron metabolism on differences in the severity of anaemia between CAPD and HD patients is limited. This is a particularly relevant aspect given the well-known benefits of recombinant human erythropoietin (r-HuEPO) in the treatment of renal anaemia and that iron supplementation is mandatory in patients with r-HuEPO hyporesponsiveness.…”
Section: Introductionmentioning
confidence: 99%